(untitled) (Economics and region, 2021)
The purpose of the article is to study the problems and priority areas of development of innovative financial market technologies that will help improve the state of economic security in Ukraine. In the financial sector of the national economy, the digital transformation is quite active; the cashless economy is actively developing. It is argued that the cashless economy is the immediate future of Ukrainian society. Non-cash payments will not only help reduce the level of shadowing of the economy, but also intensify investment processes, will be convenient for economic agents and the public. Increasing the level of financial literacy and awareness of the population is a priority aimed at accelerating the introduction of cashless. Further research will be devoted to these problems.